KUALITAS SUMBER DAYA MANUSIA DAN MODAL USAHA PENGARUHNYA TERHADAP PENGEMBANGAN USAHA UMKM - Naufal Nabawi; Basuki Basuki (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2022)
The aim of this research investigate the role of Micro, Small and Medium Enterprises(MSMEs) which are considered very important because they are able to absorb labor and become apillar of the economy for many people, but MSMEs also cannot be separated from problems thatmust be faced, including: lack of lack of quality human resources. owned, lack of business capitalowned and lack of knowledge of MSME business development. The purpose of this study was toexamine the effect of the quality of human resources, business capital, on the development ofmicro, small and medium enterprises.This research used a qualitative approach with the type of associative research. Data werecollected through a questionnaire method with a Likert scale. The number of samples used in thisstudy were 50 respondents, namely Sasirangan SMEs in Banjarmasin City. The next stage, thequestionnaire data was analyzed by multiple linear regression which had previously met thevalidity test, reliability test, and classical assumption test, then t test and F test analysis.The results showed that: (1) the quality of human resources has a significant positive effect onthe development of micro, small and medium enterprises; (2) Business Capital which has nosignificant effect on the development of micro, small and medium enterprises (3 qualities of humanresources, business capital, together have a significant positive effect on the development of micro,small and medium enterprises.